The Effect of Automotive Side Member Filling on Car Frontal Impact Performance - Salwani, Mohd Salleh; B. B., Sahari; Aidy, Ali; A. A., Nuraini (Faculty Mechanical Engineering, UMP, 2014)
To achieve lightweight design while retaining its crash performance, aluminum alloy component filled with foam has been adopted as an alternative lightweight material. In the paper, the effect of different type of filling on the automotive side member is studied. Impact performance is compared in terms of the energy absorbing capability and also its occupant injury. It was shown that the partially filled side member having values of 513.6 (HIC15), 677.3 (HIC36), 807.2 (CSI) and weight of 5.45 kg is found to yield lower potential of injury, and higher SEA compared to the empty side member. Even though the fully filled side member shows remarkable performance in terms of HIC, but it increases the chances of injury to the chest (CSI).